Adoption of Dairy Farming Technologies by the Farmers of Nagaur District of Rajasthan - Kumawat, S. R.; Verma, M. P. (Indian Journal of Extension Education, 2016)
The present study was conducted in Nagaur district of Rajasthan to know the adoption level of farmers regarding dairy farming technologies. In all 180 farmers were selected randomly from three block of the Nagaur district. The result of the study indicated that adoption level of farmers regarding improved breed of buffalo (45 %), Dry fodder (86 %) feeding of concentrate during lactation (45%) chaffing of fodder (58 %) colostrums feeding to newly born calves (47 %), and drinking water (72%) were quite high. The adoption of dairy farming technologies was positively and significantly related with thirteen independent variables viz. Age, Education, Family size, dairy experience, organization participation, land holding, livestock possession, annual income, economic motivation, market orientation, scientific orientation and knowledge of improved dairy management practices at 0.01 level probability